Preliminary assessment of the quantitative relationships between testicular tissue composition and ultrasonographic image attributes in the ram - Ahmadi, B.; Mirshahi, A.; Giffin, J.; Oliveira, M. E F; Gao, L.; Hahnel, A.; Bartlewski, P. M. (Elsevier, 2013)
This study examined the relationships between gross chemical composition and ultrasonographic characteristics of the ram testes. Ten testes from sexually mature Karakul rams were scanned ex situ with an 8-MHz linear-array transducer, in a transverse and longitudinal plane. All ultrasonograms were saved as digital images and subjected to computerized analyses. Crude protein content was determined by the Kjeldahl method, moisture was determined with an oven-drying method, and fat was measured by the Soxhlet extraction of dried samples. Mean pixel values (r = -0.64, P = 0.04), pixel heterogeneity (standard deviation of pixel values; r = -0.64, P = 0.04) and maximum pixel intensity (r = -0.76, P = 0.01) were all negatively correlated with parenchymal protein content. Pixel heterogeneity correlated directly with extractable lipids (r = 0.66, P = 0.02). The quantitative correlations between echotextural and biochemical parameters found in the present experiment confirm the utility of ultrasonographic imaging combined with computer-assisted image analysis for determining changes in testicular histophysiology. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Chemical composition; Image analysis; Ram; Testis; Ultrasonography